INDEX OF ACTIVE TECTONICS IN BUOL WATERSHED, BUOL REGENCY CENTRAL SULAWESI PROVINCE - Sukardan Tawil (Fakultas Teknik UMMU, 2019)
Sulawesi Island is one of the Indonesian islands located at the meeting of three large plates. Sulawesi Island consists of four arms of the North Sulawesi arm, the East Sulawesi arm, the South East Sulawesi arm and the South arm. Buol depression is a a product of tectonic activity in North Sulawesi's arms. This tectonic activity is able to reactivate the inactivity faulting. The faults in this area are expressed by the geomorphological conditions of Buol watershed.Therefore, an approach to identify tectonic activity in the research area through quantitative analysis (morphometry) is required. The research sites are located in Buol watershed, Buol Regency, Central Sulawesi Province.Morphometric analysis used to identify Index of active tectonics (IAT) with six parameters, Stream Lenght Gradient Index (SL), Drainage Basin Asymmetry (AF), Hypsometric Integral (HI), Ratio of Valley Floor Width to Valley Height (Vf), Drainage Basin Indice (Bs) and Mountain-Front Sinuosity (Smf). Based on the plotting results of the cross-elevation of Buol watershed, the hipsometric curve of 17 sub watershed in Buol watershed shows the mature stage curve pattern.Based on the parameters of Index of active tectonics (IAT) , it can be concluded that 17 sub watershed of the Buol watershed has a of moderate and low tectonic activity which may still be affected by active fault in the research area.